A 6(10) kV Cable Section Reliability Assessment Model Including Power Distribution Network Configurations and Relay Protection Circuits. (2015) - Korzhov, A.V.
Abstract: Urban power distribution network reliability depends on the resource of 6 (10) kV cables, which are its longest element. In the context of long-term operation of the distribution network, it is necessary to know when the cable network must be renewed to avoid damage, with due account of network configurations and regimes. The relevance of retrospective analysis and developong forecast methods is pointed out in the reliability concepts of the electricity industry. A number of statistical models are known. However, the reliability indicators of their operation in the distribution network must be assessed comprenehsively to improve the functioning of the existing cable network, taking into account their conditions, network configuration, and relay protection circuits. A model based on the Monte-Carlo method has developed in the LabVIEW software environment so as to estimate the probability of no-failure operation of an urban area cable section, and/or to identify renovations required to reduce the failure rate. The model permits testing different combinations of the failure rate parameters, thus producing "rich" statistical material. Cable line failure rates and urban distribution network configurations are obtained via retrospective analysis. The developed model can be applied to such cable networks.